HISTOPATOLOGICAL CHANGES OF WHITE RATS' SKIN CAUSED BY APPLICATION OF MIMOSIN FROM SIMPLISIA OF THE LAMTORO LEAF - Dwi Muslifah Nur Hijayani; I Ketut Berata; Ni Nyoman Werdi Susari (Buletin Veteriner Udayana, 2024)
Mimosine is one of the substances contained in lamtoro (Leucaena leucocephala) leaves. The toxic effect of mimosine on livestock is highly dependent on the concentration of mimosine in feed ingredients and the length of time livestock consume feed high in mimosine. This study aims to determine the histopathology of white rat skin exposed to mimosine compounds with different doses. This study used male white rats with Wistar strain, 2 months old and 300-350 g body weight. The 20 rats used were divided into four treatment groups, namely P0 (negative control, P1 (positive control, given standard mimosine 5 mg/head/day), P2 (given lamtoro leaf simplisia at a dose of 50 mg/head/day orally), P3 (given lamtoro leaf simplisia at a dose of 150 mg/head/day). On the 15th day of necropsy, the skin organs were taken and fixed using 10% NBF. After the skin organs were fixed, histopathology preparations were made using HE staining. Histopathologic examination was performed including three lesion variables: hair follicle necrosis, congestion, and inflammation. The severity of the lesions was scored as 0, 1, 2, and 3 for normal, mild, moderate and severe lesions, respectively. Data were then analyzed using Kruskal-Wallis and Mann-Whitney non-parametric tests. The results showed that exposure to mimosine from lamtoro leaf simplisia did not cause hair loss in experimental animals as it does in cattle. However, exposure to mimosine in P1 (5 mg/head/day) and P3 (150 mg/head/day) caused histopathological skin lesions in the form of congestion, necrosis, and mild inflammation. The results showed that exposure to mimosine from lamtoro leaf simplisia did not cause hair loss in experimental animals as it does in cattle. However, exposure to mimosine in P1 (5 mg/head/day) and P3 (150 mg/head/day) caused histopathological skin lesions in the form of congestion, necrosis, and mild inflammation. The conclusion of the study is that mimosine compounds from lamtoro leaf simplisia cause histopathological changes in white rat skin tissue, especially congestion lesions. However, there was no difference in the effect of mimosine administration from lamtoro leaf simplisia between a dose of 50 mg/head/day and a dose of 150 mg/head/day on the histopathology of rat skin tissue. Further research needs to be done on the effect of exposure to mimosine from lamtoro leaf simplisia with higher concentrations.